Predominant characteristics of organizational learning that influence the labor well-being of teachers in Peru - Angulo Paredes, Sarita Angélica (2021)
The purpose of the research was to identify the predominant dimension of organizational learning that influences the labor well-being of secondary education teachers -Lima (Peru). The research presented the quantitative approach, basic-substantive type, non-experimental design of cross-sectional, correlational-causal. The sample consisted of 200 teachers chosen by simple random probability sampling, to whom the organizational learning and work well-being surveys validated by Cronbach's Alpha (0.945 and 0.858, respectively) were applied. The results were obtained by means of the Nagelkerke R squared model, generating the value of 0.727 that verified that the estimated model was adequate. Likewise, the results of the study were processed by statistical non-parametric logistic regression. It was concluded that organizational learning influenced job well-being; Likewise, it was determined that the disposition to work, availability of resources and recognition in correspondence to the work (organizational learning conditions) influenced the work well-being of teachers.